Penggunaan Metode Uswah Hasanah Dalam Mengembangkan Nilai-Nilai Moral dan Agama Anak Usia 5-6 Tahun di RA Al-Huda Wargomulyo Kecamatan Pardasuka Kabupaten Pringsewu - Wardah Anggraini; Syafrimen Syafril; Syaiful Anwar (STAI Terpadu Yogyakarta, 2020)
Development of moral and religious values is the ability to behave, behave and act. One metshod that can develop moral and religious values is the uswah hasanah method. Giving uswah hasanah is an activity carried out by setting a good example for children. The purpose of this study was to determine the use of the uswah hasanah method in developing moral values and religion. This research was conducted using a qualitative descriptive approach (case study) involving 2 teachers. Data collected through observation, interviews and documentation. The results of this study indicate that the use of the uswah hasanah method in developing moral and religious values of children is memorizing short letters, memorizing Arabic vocabulary and daily prayers and practicing duha prayer to carry out religious activities, practicing fasting and alms to carry out deeds good deeds, courtesy in behaving to older people, greeting and shaking hands, apologizing when done wrong.